2007
DOI: 10.1021/la700543f
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Dicarboxylic Acids by Clay Minerals as Examined by in Situ ATR-FTIR and ex Situ DRIFT

Abstract: The adsorption of dicarboxylic acids by kaolinite and montmorillonite at different pH conditions was investigated using in situ attenuated total reflectance Fourier transform infrared (ATR-FTIR) and ex situ diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy. The sorption capacity of montmorillonite was greater than that of kaolinite. Adsorption of dicarboxylic acids (succinic acid, glutaric acid, adipic acid, and azelaic acid) was the highest at pH 4 as compared with those at pH 7 and 9. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 50 publications
9
72
0
Order By: Relevance
“…However, in the ATR-FTIR spectrum of pentanedioic acid (absorbed on the coated (Scheme 2 b ). [19,20,24] As shown in Figure 3 ) . This difference signified that both of the carboxylate groups coordinated to TiO 2 through the same bidentate chelating mode (Scheme 2 c).…”
Section: Nature Of Pre-coordination Of Dicarboxylic Acids On the Tio mentioning
confidence: 78%
“…However, in the ATR-FTIR spectrum of pentanedioic acid (absorbed on the coated (Scheme 2 b ). [19,20,24] As shown in Figure 3 ) . This difference signified that both of the carboxylate groups coordinated to TiO 2 through the same bidentate chelating mode (Scheme 2 c).…”
Section: Nature Of Pre-coordination Of Dicarboxylic Acids On the Tio mentioning
confidence: 78%
“…The inducement of inner-sphere coordination on a mineral surface is due not only to dehydration but also to significant decreases in pH upon drying. This can be discerned from the observation of Kang and Xing (2007) that inner-sphere complexation was favored at lower pH, and the work of Dowding et al (2005) and Clarke et al (2011) illustrating drastic pH decreases (hydrogen ion activity increased 1000-fold) with increased drying. Although the spectra of powders or pressed pellets is applicable for understanding interactions under extremely dry conditions, it may provide false information regarding the types of surface complexes formed under well hydrated conditions.…”
Section: Organic Molecule Interactions With Mineral Surfacesmentioning
confidence: 99%
“…Although the interference from water in a spectrum is typically diminished in transmission FTIR and DRIFTS analyses due to dehydration of the sample, these methods may provide inaccurate representation of interactions on a hydrated mineral surface. Kang and Xing (2007) and Kang et al (2008) noted that the carboxylic acid function groups of organic acids tend to form outer-sphere complexes with metal centers on minerals when the spectra of pastes were collected using in situ ATR-FTIR. However, inner-sphere complexes were more predominant in the DRIFTS spectra of freeze-dried samples as noted by shifts in the asymmetric COO − stretch to higher frequencies.…”
Section: Organic Molecule Interactions With Mineral Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…7) suggests that preferential adsorption of the carboxylic component was facilitated by the pre-existing soil-DOM phases of the dried soil. Prior work has shown that soil drying may promote conformational changes in pre-adsorbed DOM that promotes preferential desorption of O-alkyl relative to further inner-sphere coordination of carboxyl components (Kang et al, 2008;Kang and Xing, 2007). Additional support for the formation of inner-sphere carboxyl complexes is from the higher preferential adsorption of carboxyl over amide as observed in FTIR spectra of wet-dry compared to continuously wet treatments (Fig.…”
Section: Discussionmentioning
confidence: 77%